Beyond the "Ferguson Effect" on Crime: examining its Influence on Law Enforcement Personnel - Hoffman, Chrystina (Crime & delinquency, 2023)
The purpose of the current study is to examine the influence tensions over high-profile officer-involved shootings have had on Atlanta police officers? ability to do their jobs and whether these impacts vary by officer race. Data was collected between August and October of 2016. A total of 241 police officers across six zones completed the self-administered survey. Findings indicate that while white officers, on average, felt the impacts of recent tensions surrounding officer-involved shootings more strongly, non-white officers were more likely to say they would leave policing if offered a better paying job in another field. This study provides insight into racial differences in the impacts of recent tensions and protests over fatal officer-involved shootings.